TI_GERICHTE 52.2015.519 vom 5. August 2016 , Licenza edilizia. Indice di sfruttamento. Superficie utile lorda. Superficie dei muri - TI Tribunale d'appello (2016)
Licenza edilizia. Indice di sfruttamento. Superficie utile lorda. Superficie dei muri